The importance of using quality indicators in nursing care - Silveira, Thaizy Valânia Lopes; Prado Júnior, Pedro Paulo do; Siman, Andréia Guerra; Amaro, Marilane de Oliveira Fani (Revista Gaúcha de Enfermagem, 2015)
To investigate the opinion of hospital nurses on the use of quality indicators for nursing care. Research based on the qualitative approach, conducted with 41 nurses from two charity hospitals in Minas Gerais, from September to October 2013. Interviews with a semi-structured script were used to collect data. The empirical data were organized by means of content analysis. Indicators are important for assessing the provided care, for improving the The difficulties encountered when using these indicators revealed the following constituent elements: lack of time, inadequate number of professionals and lack of knowledge on the subject. It was concluded that nurses understand that indicators are instruments that enable evaluations and improvements, but their understanding of how to use these instruments is incomplete and fragmented.

Investigar la opinión de los hospitales las enfermeras en el uso de indicadores de calidad de los cuidados de enfermería. Las investigaciones realizadas por el enfoque cualitativo realizado con 41 enfermeros de dos hospitales filantrópicos en Minas Gerais en el período septiembre-octubre de 2013. Se utilizó entrevistas con guión semiestructurado. Los datos empíricos se organizaron de acuerdo con el análisis de contenido. Se encontró que los indicadores son importantes para la evaluación de la atención, mejorar la calidad de la atención y el desarrollo de estrategias para alcanzar las metas. Entre las dificultades encontradas en el uso de indicadores, que era posible enumerar los siguientes componentes básicos: la falta de tiempo, el número insuficiente de profesionales y la falta de conocimiento sobre el tema en cuestión. Llegamos a la conclusión de que las enfermeras entienden los indicadores como herramientas de evaluación y mejoras, sin embargo, tienen una comprensión incompleta y fragmentada de cómo utilizarlos.
Keywords: Quality indicators; Health care; Nursing care; Nursing